Les « dissidences non dissidentes » du Front Polisario dans les camps de réfugiés et la diaspora sahraouis - Carmen Gómez Martín; Cédric Omet (L’Année du Maghreb)
The increase of social inequality and emigration has disrupted Sahrawi society at the beginning of the XXI century. Sahrawi society is today restructuring under the pressure of new political organizations formed by young people within three contexts : occupied territories, refugee camps and expatriate national groups. Twenty years of diplomatic failures have led to the emergence of groups who have re-appropriated the rhetoric of a call to arms and the challenge to existing power structures. In this article we show that such organizations, defining themselves as the “non-dissident dissidents” of the Polisario Front, are reshaping the Sahrawi political camp, opening a way to internal opposition and the possibility of political change at the head of Polisario Front, and introducing further uncertainty in the resolution of the conflict in the Western Sahara.